Case Report: HGF and NF1 mutations as putative bypass mechanisms of MET inhibitor resistance in hepatocellular carcinoma: a case study - Chen, Zhitao; Luo, Shan; Gu, Yangjun; Li, Qiyong (Frontiers in Pharmacology, 2025)
BackgroundHepatocellular carcinoma (HCC) is a highly aggressive liver cancer with poor prognosis, often associated with resistance to treatment. MET amplification has been identified as a potential therapeutic target, but resistance to MET inhibitors, such as crizotinib, remains a significant challenge. This study aims to explore the molecular mechanisms underlying resistance to MET inhibitors in MET-amplified HCC.MethodsWe present a case of advanced HCC in a patient with MET amplification treated with crizotinib. After initial tumor regression, disease progression occurred. Genetic analysis using next-generation sequencing (NGS) was performed on biopsy samples taken before and after progression to identify mutations associated with resistance.ResultsNGS revealed the loss of MET amplification and identified HGF and NF1 mutations as potential bypass mechanisms. Specifically, a missense mutation in HGF (p.G401A) was observed, which may enhance ligand-receptor binding, while an NF1 mutation (p.M546L) may permit sustained MAPK and PI3K activation despite MET inhibition. These observations are preliminary and require validation in larger patient cohorts.ConclusionOur findings suggest that acquired resistance to MET inhibitors in MET-amplified HCC may involve clonal evolution and activation of compensatory signaling pathways. These insights highlight the need for dynamic molecular surveillance and the development of strategies targeting multiple pathways to overcome resistance and improve patient outcomes.